A novel hypothesis on the relationship between maternal education and obesity in children; the mediating role of maternal and child self-control—ABIS a population-based cohort study - White, Pär Andersson; Ludvigsson, Johnny; Jones, Michael P.; Faresjö, Tomas (Frontiers in Public Health, 2025)
BackgroundLow socioeconomic status, measured by maternal education, increases the risk of obesity in children in high-income countries. This paper presents our hypothesis that self-control mediates the observed association.MethodsData from the All Babies in Southeast Sweden (ABIS) cohort, which includes children born 1st Oct 1997–1st Oct 1999 in southeast Sweden with data on BMI, were available for N = 5,447 at age 19 out of the original cohort of N = 17,055 participants (31.9%). We estimated maternal self-control through behaviors related to self-control, first using a latent variable constructed using the variables breastfeeding duration, maternal smoking during pregnancy, maternal smoking during the first year of the child’s life, and participation with biological samples. In a second model, we also included maternal BMI. Child self-control was measured using the Hyperactivity/Inattention subscale of the Strength and Difficulties Questionnaire (SDQ).ResultsWe found that in the relationship between maternal education and BMI/obesity risk of the child at age 19, two indirect paths, maternal self-control and child self-control, mediated 85% of the effect on BMI (model 1) and 87.5% of the effect of obesity risk. Adding maternal BMI (model 2) to the latent maternal self-control variable increased the mediated indirect effect to 95% of the total effect for BMI and 94% of the total obesity risk.ConclusionWe conclude that maternal self-control and child self-control may mediate most of the effect of low maternal education on BMI/obesity at age 19. The central role of self-control in health inequality, especially for the persistence of health inequalities in the welfare state, may have important implications and should be included when theories of health inequalities are constructed. However, future studies are needed to test the hypothesis described in this paper using additional measures of self-control and executive functions.